2018
DOI: 10.1371/journal.pone.0198053
|View full text |Cite
|
Sign up to set email alerts
|

1H MR spectroscopy of the motor cortex immediately following transcranial direct current stimulation at 7 Tesla

Abstract: Transcranial direct current stimulation (tDCS) is a form of non-invasive brain stimulation that may modulate cortical excitability, metabolite concentration, and human behaviour. The supplementary motor area (SMA) has been largely ignored as a potential target for tDCS neurorehabilitation but is an important region in motor compensation after brain injury with strong efferent connections to the primary motor cortex (M1). The objective of this work was to measure tissue metabolite changes in the human motor cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
(98 reference statements)
1
14
0
Order By: Relevance
“…Exploratory post-hoc tests were not corrected for multiple comparisons to avoid a relevant enhancement of type II errors, according to Perneger 50 , and Feise 51 . This is also in accordance with other studies in the field, and thus increases inter-study comparability 52,53 .…”
Section: Methodssupporting
confidence: 92%
“…Exploratory post-hoc tests were not corrected for multiple comparisons to avoid a relevant enhancement of type II errors, according to Perneger 50 , and Feise 51 . This is also in accordance with other studies in the field, and thus increases inter-study comparability 52,53 .…”
Section: Methodssupporting
confidence: 92%
“…The majority of studies on tDCS-induced changes with respect to GABA and Glu were performed by 3 T MRI scanner and rather provide heterogeneous results that vary with the targeted cortical area 19 , 60 . While a number of studies reported the absence of tDCS induced changes of GABA or Glu level in the prefrontal 42 , 61 and motor cortex 55 , 62 , Clark et al (2011), for example, reported enhanced Glu in combination with Gln concentration after anodal tDCS over the parietal cortex. Such dissimilar outcomes may also be explained by methodological differences of MRS data acquisition by low-magnetic field strength compared to high-magnetic field strength measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Standard criteria were applied for excluding spectra with poor quality: (i) CRLB of GABA and Glu > 20%, (ii) FHWM > 25 Hz, and (iii) SNR < 8. The concentration of GABA and Glu was corrected for the proportion of grey matter within the voxel 37 , 54 , 55 . The group wise outliers of GABA and Glu concentrations, defined as greater than three times the interquartile range, from the remaining spectra were further detected using Boxplot in SPSS 24 (for Windows) and were removed.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, anodal tDCS applied over the motor cortex using various protocols has been found to cause significant decrease in GABA concentration in the ipsilateral motor cortex (Stagg et al, 2009a; Kim et al, 2014; Bachtiar et al, 2015, 2018; Antonenko et al, 2019; Patel et al, 2019). Few tDCS MRS studies have been conducted at 7 T on the same premise of the present study that sensitivity and reliability of metabolic measurements largely benefit from ultra-high magnetic fields (Stagg et al, 2009a; Kim et al, 2014; Ryan et al, 2018). Yet the results of these tDCS 7 T investigations have been variable.…”
Section: Discussionmentioning
confidence: 90%
“…Yet the results of these tDCS 7 T investigations have been variable. No changes in Glu or GABA were observed in correspondence of bihemispheric tDCS (Ryan et al, 2018), while cathodal stimulation was reported to either induce a significant decrease in Glu/Cr (Stagg et al, 2009a) or no observable Glu change (Kim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%